A Tissue Perfusion Harvest Model for Optimal Multisystem Comparisons of Pathobiology. Issue 1 (14th January 2022) - Kohut, Lauryn; Ross, Mark A; Loughran, Patricia A
Abstract: Gravity flow whole‐body perfusion maintains effective and reproducible preservation of tissue architecture critical to investigate pathobiology of multiple organs from the same specimen. The purpose of the protocols described within this article is to help the researcher optimize tissue harvest for multisystem pathobiology comparison. The protocols presented here describe tissue harvest for processing and cryopreservation to generate optimal samples for microscopy and parallel biochemical and molecular biology analysis. First, this paper outlines a protocol for tissue perfusion and organ harvest that allows the researcher multiple analysis options from the same research subject simultaneously. Second, this paper outlines a model to optimize ex‐vivo tissue fixation for precious human sample preparation. Finally, this paper outlines a methodology for freezing tissue samples to optimize their capacity for biochemical and immunohistochemical analysis. Benefits and alternative approaches to retain cellular morphology in tissue harvest and processing are discussed. Also described within each section are common technical issues to assist problem‐solving and troubleshooting. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Whole body in vivo tissue perfusion by gravity flow: preparation and surgical procedures Alternate Protocol : Human ex vivo tissue fixation Basic Protocol 2 : Freezing of tissue samples